URGENSI PENJAMINAN MUTU SEKOLAH - Kurniawan, Deni (Prodi Teknologi Pendidikan, 2014)
Abstract, human resources have a central role in the development and advancementof an organization. Human recources development is closely related to educationalinstitutions, one of which is school. In order to optimize the process education in schools, itis important to ensure school quality assurance system. The goal of this system is to fulfillthe satisfaction of education stakeholders. To find out the expectations and satisfaction ofthe stakeholders, a school can obtain information by using various alternative ways deemedsuitable with the kind of information expected and the resources owned by the school.Keywords: quality assurance, satisfaction, stakeholdersAbstrak, sumber daya manusia memiliki peranan sentral bagi pengembangan dankemajuan organisasi. Pengembangan SDM terkait erat dengan lembaga pendidikan, salahsatunya adalah sekolah. Agar proses penyelenggaraan pendidikan di sekolah bisa optimalmaka penting adanya sistem jaminan kualitas sekolah. Tujuan utama dari sistem jaminankualitas sekolah adalah agar terpenuhinya kepuasan stakeholders pendidikan. Untukmengungkap harapan dan kepuasan stakeholders sekolah bisa dilakukan melalui penggalianinformasi dengan menggunakan beragam alternatif cara yang dipandang sesuai denganjenis informasi yang diharapkan dan keberadaan sumber daya yang dimiliki sekolah.Kata Kunci: jaminan kualitas, kepuasan, stakeholders,informasi